2007
DOI: 10.1177/1352458507077175
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in multiple sclerosis: association with disease-related, behavioural and psychosocial factors

Abstract: We determined biopsychosocial correlates of general, physical, and mental fatigue in MS patients, by evaluating the additional contribution of potentially modifiable factors after accounting for non-modifiable disease-related factors. Fifty-three ambulatory MS patients, along with 28 normal controls were recruited for a cross-sectional study. Subjects completed the Multidimensional Fatigue Inventory (MFI) and Fatigue Severity Scale. Potential correlates evaluated were: disease-related factors (disease duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 54 publications
5
110
1
5
Order By: Relevance
“…Fatigue, a multifactorial entity in MS with dimensions including energy loss, sleepiness, and inability to sustain activity, 34 seems to increase cognitive complaints 35 and is associated with reduced self-efficacy. 36 Although not expressly measured in this study, fatigue has been shown to be reducible with physical activity. 6 Further exploration of the relationship between somato-affective features of depression and aerobic exercise appears warranted.…”
Section: Resultsmentioning
confidence: 63%
“…Fatigue, a multifactorial entity in MS with dimensions including energy loss, sleepiness, and inability to sustain activity, 34 seems to increase cognitive complaints 35 and is associated with reduced self-efficacy. 36 Although not expressly measured in this study, fatigue has been shown to be reducible with physical activity. 6 Further exploration of the relationship between somato-affective features of depression and aerobic exercise appears warranted.…”
Section: Resultsmentioning
confidence: 63%
“…There is evidence for an association between morphological fitness, assessed as BMI, and symptomatic fatigue in MS. In a sample of 53 participants with moderate MS (mean EDSS=3.4), a higher BMI was associated with higher scores on the Multidimensional Fatigue Symptom Inventory physical fatigue subscale (r=0.36) [44]. Collectively, the existing research suggests physiological deconditioning in multiple domains might be related with more frequent and severe symptoms of fatigue in persons with MS.…”
Section: Fatiguementioning
confidence: 86%
“…Sleep disturbances are the most disturbing. 51,52 In a recent expert review by Krupp et al, a multidisciplinary treatment approach is recommended, including cognitive-behavioural therapy, exercise therapy and substantial effort to reduce secondary fatigue-inducing factors. Based on the present review, exercise therapy seems to have an effect on MS fatigue and we suggest that exercise therapy should comprise a substantial part of the multidimensional approach.…”
Section: Effects Of Socializationmentioning
confidence: 99%